Development of an English module based on Bugis' local wisdom - Mujahidah; Wahyu Hidayat; Muhammad Zuhri Dj; Ishak (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study aims at developing high school English learning modules based on Bugis culture. This research applied Development Design Research (DDR) approach and involved several parties related to the development of the EMBOS module, namely high school English teachers and experts. Data were collected by using Focus Group Discussion. The data were analyzed qualitatively using the N-VIVO software, and the quantitative data were analyzed using the Fuzzy Delphi and Aiken's V methods. Needs analysis using the Group Interview method or Focus Group Discussion resulted in several issues or themes. The results of expert approval using the Fuzzy Delphi method found that the Mappadendang topic received approval in the song/narrative material with a Threshold (d) value of 0.038 and an average of Fuzzy Number 0.787. The topic of Mappadinding received approval on the Explanation Text/ Description Text material with a Threshold (d) value of 0.038 and an average fuzzy number of 0.787. Nene Malomo's topic on Traditional Story/Narrative Text/Reading Comprehension material with a Threshold (d) value of 0.038 and an average of Fuzzy Number 0.787. Developing an English learning module based on Bugis Local Wisdom consists of the beginning, content and the end. Experts have validated the EMBOS module. The results of expert validation indicate that this module is generally suitable for use in learning English at the high school level or equivalent. An English learning module based on Bugis local wisdom can be implemented as an alternative to bring students closer to their environment or contextual learning.